Deformation characteristics and reactivation mechanism of an old landslide induced by combined action of excavation and heavy rainfall - Dai, Zhenwei; Yang, Long; Zhang, Nan; Zhang, Chenyang; Zhang, Zhihua; Wang, Heng (Frontiers in Earth Science, 2023)
The reactivation mechanism of old landslides has been extensively studied from building load, erosion of the slope toe, heavy rainfall and slope cutting for existing research. However, previous research on the reactivation of old landslides pays little attention to the combined action of engineering disturbance and heavy rainfall is rarely studied. This paper describes an old landslide in Wushan County, Chongqing, China, that was reactivated in August 2019 due to engineering disturbance and heavy rainfall. The deformation of the old landslide was first observed in 2007 and 2008, resulting from excavation and rainfall, respectively, and remained stable for about 11 years after treatment. In August 2019, the landslide was reactivated by slope cutting and damaged anti-sliding piles at the toe, and entered a state of imminent sliding due to the concentrated heavy rainfall events that occurred from October 4 to 22, 2019. In order to reveal the deformation features and reactivation mechanism of the landslide, field investigations, drilling activities and monitoring were performed. The results showed that tectonic effects and the stratigraphic lithology were the main reasons for the formation of the old Dashuitian landslide. The cut slope and damaged anti-sliding piles at the toe of the landslide provided the sliding space and reduced the anti-sliding force, and therefore resulted in the reactivation of the landslide. Continuous intense rainfall increased the weight of the landslide, decreased the mechanical properties and increased the pore water pressure of the weak interlayer, which accelerated the deformation rate. Therefore, 1.5 million m3 of rock and soil masses slid along the weak interlayer under the action of gravity, threatening the safety of Wuliu Road, Ring Road, National Road G42 and the Wu-Da Expressway. Our research provides a theoretical basis for reducing the hazard of similar engineering projects involving slopes.